Homo Islamicus dan Imperfect State : Konsep Manusia dan Al-Madinah Al-Fadilah menurut Al-Farabi - Havis - Aravik; Achmad Irwan Hamzani (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose: This article discusses about the other side of al-Farabi, an Islamic economic thinker. With the aim that an open paradigm of thinking new in seeing al-Farabi, not only political experts and famous philosophers, but also as a reliable Islamic economic thinker.Design/Method/Approach: This article uses library-based qualitative research (qualitative research) with a qualitative descriptive approach and technical descriptive analysis and content analysis.Finding: This study was able to identify that al-Farabi was truly an Islamic economic thinker. Al-Farabi's Islamic economic thinking can be seen in his works such as the Book of Ara 'Ahl al-Madinah al-Fadilah, Kitab al-Siyasat al-Madaniyah and the Tahsil al-Sa'adah Book. Al-Farabi was one of the economic thinkers who emphasized his economic thinking on the concept of man as homo Islamicus who had an advantage in the field of reason compared to other beings (al-hayawan al-nathiq) where one of his goals was to become a perfect society (al- kalimah) and happy by doing noble actions, virtues and virtues. However, in its journey, the existence of the community formed a state that was in the form of a main state (al-Madinah al-Fadilah), a foolish state (al-madinah al-Jahilah), a fasiq state (al-madinah al-Fasiqah), a perverse country (al -madinah al-Dhallah), and a changing state (al-madinah al-Mutabaddilah). The ideal country that can manifest human happiness is the main country (al-Madinah al-Fadilah).Originality/Novelty: This research contributes to filling the 'emptiness' of Islamic economic theory, which comes from Al-Farabi's thoughts and works. This study did not become a 'copy' which informed the other side of Al-Farabi as a philosopher. But he also offers economic thinking, especially in relation to the human concept and welfare state.